Phenylethanoid and secoiridoid glycosides from the leaves of Ligustrum purpurascens. (September 2015) - Fan, Long; Liao, Cheng-Hui; Li, Shuo-Guo; Huang, Xiao-Jun; Hu, Xiao-Peng; Song, Xun; Fan, Chun-Lin; Wang, Ying; Ye, Wen-Cai; Kang, Qiang-Rong; Zheng, Kai; Liu, Li-Ping; et al.
Graphical abstract: Highlights: Two new compounds were isolated from the leaves of Ligustrum purpurascens . Structures were established on the basis of the spectroscopic methods. Compounds1 –15 were screened for their up-regulation of IFN-γ secretion. 1, 5, 6, 10, 11, 13 and15 exhibited potent stimulatory effect on IFN-γ secretion. Abstract: A new phenylethanoid glycoside (2 ) and a new secoiridoid glycoside (16 ) were isolated from the leaves of Ligustrum purpurascens together with fourteen known compounds (1 and3–15 ). The structures of the new compounds were determined by spectroscopic analyses (UV, IR, HR-ESI-MS, 1D, and 2D NMR). The absolute configuration of16 was further determined by CD analysis. All phenylethanoid glycosides were prepared and their up-regulation of IFN-γ production in mouse splenic lymphocytes was evaluated. Compounds1, 5, 6, 10, 11, 13 and15 exhibited potent stimulatory effect on IFN-γ secretion.